Palmitoylated antigens for the induction of anti-tumor CD8+ T cells and enhanced tumor recognition - Dorian A. Stolk; Sophie K. Horrevorts; Sjoerd T.T. Schetters; Laura J.W. Kruijssen; Sanne Duinkerken; Eelco Keuning; Martino Ambrosini; Hakan Kalay; Rieneke van de Ven; Juan J. Garcia-Vallejo; Tanja D. de Gruijl; Sandra J. van Vliet; et al. (Molecular Therapy: Oncolytics, 2021)
Induction of tumor-specific cytotoxic CD8+ T cells (CTLs) via immunization relies on the presentation of tumor-associated peptides in major histocompatibility complex (MHC) class I molecules by dendritic cells (DCs). To achieve presentation of exogenous peptides into MHC class I, cytosolic processing and cross-presentation are required. Vaccination strategies aiming to induce tumor-specific CD8+ T cells via this exogenous route therefore pose a challenge. In this study, we describe improved CD8+ T cell induction and in vivo tumor suppression of mono-palmitic acid-modified (C16:0) antigenic peptides, which can be attributed to their unique processing route, efficient receptor-independent integration within lipid bilayers, and continuous intracellular accumulation and presentation through MHC class I. We propose that this membrane-integrating feature of palmitoylated peptides can be exploited as a tool for quick and efficient antigen enrichment and MHC class I loading. Importantly, both DCs and non-professional antigen-presenting cells (APCs), similar to tumor cells, facilitate anti-tumor immunity by efficient CTL priming via DCs and effective recognition of tumors through enhanced presentation of antigens.